Static and dynamic structural monitoring based on optical fiber sensors - Antunes, P.
In this paper, we report the monitoring of an adobe structure with optical fiber sensors. Static and dynamic measurements were made during a destructive test on a full-scale wall, in which an in-plane cyclic force was imposed, by a hydraulic jack, until the wall collapse. An optical fiber accelerometer and a network of thirteen multiplexed displacement sensors were used to monitor the wall under test. The obtained results demonstrate that the optical fiber sensors had the capacity to monitor this large scale test, showing results similar, with a maximum relative error of 2.08 %, to the results obtained with electronic reference sensors.